Eric Craigie interviewed by Chris Sullivan and Mark Rummery in the Chris Sullivan folklore collection - Craigie, Eric, 1908-; Sullivan, Chris (Christopher Daniel), 1953-; Rummery, Mark. (1984)
Folkloric recording.
Recorded on 3 July 1984, at Moree, N.S.W.
Digital master available
Keywords: Craigie, Eric, -- 1908- -- Interviews; Aboriginal Australians -- New South Wales -- Mungindi -- Interviews; Folk musicians -- New South Wales -- Interviews; Folk songs, English -- New South Wales -- Moree; Folk dance music -- New South Wales -- Mungindi; Folk music -- New South Wales -- Mungindi; Accordion music; Folk musicians; Folk singers